Performance Comparison of MicroSD and eMMC Storage in a Single-Node Hadoop Environment - Muhammad Arfah Asis; Lutfi Budi Ilmawan; Nur Ikhwan Alfiansyah; Rahman Ramadhan (G-Tech: Jurnal Teknologi Terapan, 2025)
This study analyzes the performance comparison between eMMC and MicroSD storage in a single-node Hadoop environment, focusing on data processing efficiency using the Terasort and TestDFSIO benchmarks. In this experiment, four different data sizes, namely 500MB, 1GB, 1.5GB, and 2GB, were tested to evaluate how well each storage type handles data processing. The test results show that eMMC consistently outperforms MicroSD across all tested dataset sizes. The larger the data size processed, the more significant the performance comparison between the two storage types. At a data size of 2GB, eMMC is almost four times faster than MicroSD, showing a very clear advantage in processing efficiency. In addition, the results of the TestDFSIO test support this finding. In the test, eMMC shows a write speed that is 50% higher than MicroSD, and a read speed that is almost twice as fast at a data size of 10GB. This performance difference confirms that eMMC has a better capacity to handle large data, which is an important factor in applications that require intensive processing. The findings emphasize that eMMC offers better performance and stability than MicroSD, making it a more suitable choice for applications requiring high speed and efficiency in Hadoop environments. This research is expected to provide valuable insights for developers and researchers considering optimal storage solutions for big data processing.